The mechanism of the defect centers influence on the paraelectronin-to-incommensurate phase transition in rubidium-potassium zinc chloride crystals - Trubitsyn, M.P.; Antonenko, A.M. (Functional Materials, 2007)
The (x-T) phase diagram of midex (Rb₁₋ₓKₓ)₂ZnCI₄ crystals has been studied. The effect of impurity defects on the paraelectronic-to-incommensurate phase transition has been shown to be due to straining compression of the Rb₂ZnCI₄ structure cell at K⁺ ions substitution for Rb⁺.